PROFESSIONALISM OF EDUCATORS IN LEARNING DEVELOPMENT - Sehan Rifky; Sepling Paling; Opan Arifudin; Putu Satya Narayanti (International Journal of Teaching and Learning, 2024)
This comprehensive literature review explores the multifaceted dimensions of optimizing educator professionalism in learning development. Digging into the field of an educator who must have and master his competencies and at the same time know his rights and obligations so that he becomes a truly professional educator. This review synthesizes existing research, identifies trends, and offers insights for educators, policymakers, and researchers. The reason behind this exploration lies in the urgency to find out the professionalism of a teacher, namely: the position of professional educators, realizing professional educators, and the development of learning models by professional educators. This review examines models of teacher professional development with the aim of providing teachers with options to improve their professionalism. If teacher professionalism improves, it is certain that the quality of education can also increase.